Determination of the environmental economic value of a tropical typical dairy farm of Mayabeque, Cuba - Báez, Nadia; Lok, Sandra; Gómez, C. (Cuban Journal of Agricultural Science, 2021)
To determine the environmental economic value of a typical dairy farm in Mayabeque province, based on the exploitation of a silvopastoral system with Leucaena leucocephala, after 20 years of establishment, the main environmental functions of the agroecosystem were identified, taking into account the theory of total economic value. According to the value category, six functions were identified: milk production, carbon sequestration, nitrogen fixation, soil fertility, soil quality, obtaining renewable energy and biodiversity. Different valuation techniques were applied, depending on each environmental function. The total economic value provided by the livestock ecosystem in the studied year was 52 189.15 USD, which is much higher than if only its productive value had been considered. This research demonstrated the importance of taking into account the environmental economic valuation, as an instrument to achieve the sustainable and integral management of all the components that make up the livestock ecosystems, so that it is possible to achieve their resilience. Keywords: environmental functions, livestock, silvopastoral system, total economic value